Water resources in inland regions of central Asia: Evidence from stable isotope tracing - Li, Zongxing; Gui, Juan; Wang, Xufeng; Feng, Qi; Zhao, Tongtiegang; Ouyang, Chaojun; Guo, Xiaoyan; Zhang, Baijuan; Shi, Yang (Journal of Hydrology, 2019)
Complex hydrological processes affect valuable water resources in inland regions across arid central Asia. Historically, this was a critical part of the Silk Road, and it is now named the modern Silk Road Economic Belt. Using the Qilian Mountains and Hexi Corridor in China as a case-study of the inland region, we collected a total of 2311 water samples from the area and performed a comprehensive investigation of the water cycle. Results from stable isotope tracing indicate clear spatial patterns. In the upstream mountainous regions, glacier snow meltwater becomes groundwater at the periglacial belt. Supra-permafrost water develops into river runoff in the permafrost region. There are also frequent exchanges between groundwater and river runoff along the vegetation belt. In the middle/downstream region, river runoff becomes groundwater. Throughout these processes, both river runoff and groundwater are consumed by evapotranspiration, are recycled, and make a substantial contribution to precipitation. Overall, the upstream mountainous region is a critical part of the water resources. The cryosphere belt accounts for 44% of the mountainous region but contributes to about 80% of water resources. Recycling of moisture also plays an important role. During the summer months (May to September) moisture recycling accounted for 24% and 14% of precipitation in upstream and middle/downstream regions, respectively. The findings from the stable isotope tracing provide insights into hydrological processes and can help improve water management in inland regions of Central Asia.